2015
DOI: 10.1021/acssuschemeng.5b00198
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant IR Reflecting Yellow Colorants in Rare Earth Double Molybdate Substituted BiVO4 Solid Solutions for Energy Saving Applications

Abstract: Brilliant IR reflecting yellow colorants are developed in rare earth double molybdate substituted BiVO 4 solid solutions. Li 0.10 RE 0.10 Bi 0.8 Mo 0.2 V 0.8 O 4 (RE = La, Pr, Sm, Gd, Tb, Dy, Y, Yb and Lu) pigments are prepared by a conventional solid-state reaction route and their optical, structural and morphological properties are analyzed. X-ray diffraction analysis confirms the tetragonal scheelite phase formation in the series. These pigments have a strong optical absorption in the UV-blue light waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…The observed color coordinates (L*, a*, and b* parameters) were compared with BiVO 4 , which is also a yellow colored compound. [29] The data are presented in Table S5, S6. The BiMgVO 5 and BiCdVO 5 compounds compare well with the reported BiVO 4 .…”
Section: Bicdvomentioning
confidence: 99%
“…The observed color coordinates (L*, a*, and b* parameters) were compared with BiVO 4 , which is also a yellow colored compound. [29] The data are presented in Table S5, S6. The BiMgVO 5 and BiCdVO 5 compounds compare well with the reported BiVO 4 .…”
Section: Bicdvomentioning
confidence: 99%
“…Al 2 O 3 was used as a white reference and the test range was 300–2500 nm. ASTM G173-03 was taken as a reference for calculating the NIR reflectance ( R ) of the pigments and their coatings in the wavelength range from 700 to 2500 nm, and the main formula is: , where i (λ) is the solar spectral irradiance (w·m –2 ·nm –1 ) and r (λ) is the spectral reflectance obtained from the experiment.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Recently, the yellow pigments based on iron and tungsten codoped La 2 Ce 2 O 7 and BiVO 4 -coated mica–titanium oxide pigment have been reported. Notably, Rao et al also reported a suite of BiVO 4 -based brilliant yellow pigments and Y-doped Bi 2 MoO 6 yellow pigments, , which are friendly alternatives to toxic pigments (PbCrO 4 -based pigment and PbSbO 3 pigment). , These pigments with high near-infrared reflectance can serve as cold pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, the occupied 4f band in Yb oxide locates above the O 2p band; hence, the band-gap energy can be determined by 4f−d transition. Rao et al 18 stated that the increase of atomic number of the rare earth became gradually lowered to the 4f electronic level, finally approaching the valence band, which resulted in an increase of the band-gap energy. Whereas the band-gap energy of Gddoped pigment is 2.40 eV, it is higher than 2.37 eV of Yb (with a higher atomic number than Gd-doped pigment in this study).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation